Understanding Culture through Textbooks: A Study on Teacher Cognition and Cultural Representation in Indonesian EFL Classrooms - Hidayati, Salila Prasidya; Falianda, Fallianda; Firdausiyah, Hurrotul (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2026)
This study investigates how cultural representation is constructed in Indonesian EFL textbooks and mediated through teacher cognition in classroom practice. Using a qualitative case study design, the research analyzed five selected chapters from the Grade 10 English textbook Work in Progress and conducted semi-structured interviews with three EFL teachers in Gresik, East Java. The study employed qualitative content analysis, multimodal discourse analysis, and teacher cognition theory to examine textual, visual, and pedagogical dimensions of culture. The findings indicate that globalized or modernized culture dominates textbook representation, while Indonesian culture is embedded implicitly through collaborative classroom practices and native-speaker culture receives limited representation. The study also reveals that teachers play an important mediating role in interpreting cultural content. However, classroom practices tend to prioritize communicative competence over explicit intercultural reflection due to curriculum demands, assessment orientation, and time constraints. Consequently, cultural learning remains largely implicit and less critically developed. The findings suggest that cultural representation in EFL classrooms emerges dynamically through the interaction between materials, pedagogy, and teacher cognition. This study highlights the importance of explicit intercultural pedagogy and teacher preparation in supporting intercultural competence development in Indonesian EFL contexts.